ANALISIS PENYELESAIAN HUKUM SENGKETA HAK MEREK ASING TERKENAL TERHADAP PEMBONCENGAN REPUTASI - Andiza, Dina; Nadira, Ida (The Juris, 2025)
Legal protection for well-known trademarks is very important because trademarks not only function to distinguish similar goods and/or services, but also have an economic function. In the world of trade, there are often acts of reputation-hijacking which are motivated by various factors. The type of research used in this study is Normative Legal Research with the research approach used is the Case Approach. With the nature of the research, namely Descriptive Research and based on the form of research used is Prescriptive Research. Data sources are obtained through Secondary Data, which are divided into Primary Legal Materials and Secondary Legal Materials. The analysis is carried out qualitatively, namely by analyzing the data that has been obtained through a general and comprehensive description and then concluding the results of this study. Protection of foreign well-known trademarks nationally is regulated in Indonesian legislation, namely Law Number 20 of 2016 concerning Trademarks and Geographical Indications which is carried out in two ways, namely preventive legal protection and repressive legal protection. The legal considerations by the Judge in Decision Number 29/Pdt.Sus/Merek/2019/PN Niaga Jkt.Pst in determining bad faith in the registration of the Superman character by the Defendant (PT. Marxing Fam Makmur) did not show any distinguishing value between the Plaintiff's Superman and the Defendant's, which is a form of indicator of bad faith from the Defendant.